Teori dan fakta dalam ilmu sebagai landasan untuk memahami kebenaran ilmiah - Khulifah, Nur (Maliki Interdisciplinary Journal, 2026)
Scientific theories serve as conceptual frameworks guiding the understanding of facts, while empirical evidence provides the foundation to verify and strengthen these theories. Scientific truth emerges from the interaction between theory and facts through a systematic, critical, and measurable scientific methodology. The epistemological approach emphasizes that scientific truth is not merely a literal correspondence between theory and reality, but also encompasses the validity of reasoning, logical consistency, and the theory’s ability to comprehensively explain phenomena. This integration forms a crucial foundation for the development of modern knowledge, ensuring that every scientific claim can be justified both rationally and empirically.